Potentials Challenges of Twenty-First Century Pedagogies in Nigeria - Ajadi, Olugbenga (Papanda Publisher, 2024)
The concept of 21st-century pedagogies is the creative use of technological-aided teaching methods for the benefit of the students based on the prevailing situation. The pedagogies include the use of technology integration, collaborative learning, student-centred learning, flipped classroom and gamification and game-based learning usually student-centred. The concept of pedagogy in Nigeria, as in many other countries, refers to the strategies, methods, and approaches employed in the teaching and learning process. The paper identified skills development, technology integration, increased student engagement, collaborative learning and teacher professional development as some potential that significantly contribute to enhancing the quality of education and equipping students with employable skills needed to succeed in the world of work. The paper identified technology barriers, teacher training and professional development, large class sizes, curricular rigidity, resistance to change and limited resources as some of the challenges confronting the use of 21st-century pedagogies in educational institutions in Nigeria. However, policy reforms, teacher training and professional development, technology integration, partnerships and research and monitoring are suggested as remedial plans to improve the use of 21st-century pedagogies in Nigerian schools.